An Application of Potential Estimates to A Priori Bounds for Elliptic Equations. (24th February 2016) - Mamedov, Farman; Monsurrò, Sara; Transirico, Maria
Abstract : A potential estimate type approach is used in order to obtain some a priori bounds for the solutions of certain classes of Dirichlet problems associated with nondivergence structure elliptic equations.